Pengukuran Kepuasan Pengguna GRAB di Palembang Menggunakan Metode EUCS - Luh Ariningsih; Megawaty Megawaty (Prodi Ilmu Komputer Universitas Bumigora, 2022)
In the application of information technology today, a lot of technology is developing rapidly to facilitate human work activities. Similar to an information system in the transportation sector, it has now been transformed into a more practical one. One of the Grab applications, which is an application to serve the community in carrying out daily activities such as delivery, delivery of goods, or ordering food. However, in its application to the community, the level of community satisfaction with the use of the application is unknown, it is necessary to analyze the level of satisfaction in using the application, especially the Grab application in Palembang City. This requires a system testing method that can measure the level of user satisfaction with the system used, this method is the End-User Computing Satisfaction (EUCS) method which is a method of measuring the level of user satisfaction with this Grab application and uses quantitative research in data collection of respondents as well as analysis. The respondents of this study are users and drivers who use the Grab application in Palembang City. The results obtained from this study are how the level of satisfaction of Grab application users in Palembang City which is based on the results of the partial test on the variables Content, Accuracy, Format, Ease of Used, Timeliness, Security, Speed ​​of Response has an influence on the End User Satisfaction variable.